Indigenous Religions Strategy in Maintaining their Belief - Iwan Setiawan; Irfan Goffary; Mohamad Hamim (International Journal of Islamic Khazanah, 2020)
The purpose of this study is to discuss the patterns of strategy adherents of the Madrais or the Djawa Sunda Religion (ADS) in Cigugur, Indonesia, in maintaining their trust. This study uses a qualitative approach to the descriptive-analytic method through literature studies. Data obtained through the review of the literature and then analyzed using content analysis (content analysis) using Miles and Crow's theory of "organizational strategy." The results showed that the pattern of the strategy of adherents of the teachings of Madrais in maintaining its beliefs seen in several ways, namely: the model of prospectors, defenders, analyzers, and reactors. The prospector pattern means forming a new form of organization. The model of defenders means to survive for the stability of the organization's existence. Pattern analyzers mean dealing with internal consolidation to find an organization's safe position. Finally, the pattern of reactors is forced to succumb because of external threats and pressures and is unable to fight them.